2009
DOI: 10.1007/s10071-009-0283-3
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of learning spatial relations among locations by visual cues: generality across spatial configurations

Abstract: Spatial pattern learning permits the learning of the location of objects in space relative to each other without reference to discrete visual landmarks or environmental geometry. In the present experiment, we investigated conditions that facilitate spatial pattern learning. Specifically, human participants searched in a real environment or interactive 3-D computer-generated virtual environment open-field search task for four hidden goal locations arranged in a diamond configuration located in a 5 x 5 matrix of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The use of a virtual environment lent itself well to such an investigation because of the ease in environmental manipulation coupled with the similarity of mechanisms utilized in real and virtual environments (see Sturz, Bodily, Katz, Kelly, 2009;Sturz, Brown, & Kelly, 2009;Sturz, Kelly, & Brown, 2010). To this end, we trained two groups of participants to find a location uniquely specified by both local (i.e., short wall left, short wall right, obtuse corner angle) and global (i.e., right side of principal axis) geometric cues in either a small or a large trapezoid-shaped virtual enclosure (see Fig.…”
mentioning
confidence: 99%
“…The use of a virtual environment lent itself well to such an investigation because of the ease in environmental manipulation coupled with the similarity of mechanisms utilized in real and virtual environments (see Sturz, Bodily, Katz, Kelly, 2009;Sturz, Brown, & Kelly, 2009;Sturz, Kelly, & Brown, 2010). To this end, we trained two groups of participants to find a location uniquely specified by both local (i.e., short wall left, short wall right, obtuse corner angle) and global (i.e., right side of principal axis) geometric cues in either a small or a large trapezoid-shaped virtual enclosure (see Fig.…”
mentioning
confidence: 99%
“…This result seems counterintuitive in that pattern A should have provided visual cues, or direct internal (i.e., box edges) and external (e.g., wall colour) references for the macaws to locate the food. The use of visual cues is expected to enhance spatial pattern learning, as has been shown in, for example, human participants showing better performance when a visual cue is associated with either rewarded or non-rewarded locations [57]. While a previous study investigating spatial pattern learning in rats has also shown that visual cues facilitated rats to not revisit locations where they had retrieved rewards, visual cues did not necessarily enhance their spatial pattern learning [58].…”
Section: Discussionmentioning
confidence: 93%
“…Other research also using rats on a radial maze (Brown & Wintersteen, 2004) or in a pole task (Brown & Giumetti, 2006) and humans (Sturz, Brown, & Kelly, 2009;Sturz, Kelly, & Brown, 2010) using a variation of the pole task in both real and virtual environments has provided additional evidence that visual cues do not overshadow pattern cues. In fact, in the experiments that used humans, there was evidence that visual cues actually potentiated learning about pattern.…”
Section: Discussionmentioning
confidence: 99%